PENGARUH KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP PENJUALAN DI SWISS-BELHOTEL DI JAYAPURA - Mugiati, Mugiati; Wadjo, Muhammad Amin (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2023)
Research methods used in this research is quantitative method. The quantitative method is a method of research that is based on a questionnaire, which is used to examine the population and the particular sample, data collection using research instruments, quantitative data analysis / statistics, with the aim to test the hypothesis that has been set. Results of research conducted to prove that there is a positive and significant influence between the quality of service to the level of sales. It can be seen from the ttabel> thitung (3.158> 1.670) with a significantly by 0.001 <0.05. The results of this study showed a significant relationship between the quality of service to the level of sales. This means that the quality of services provided by the Swiss-Bel Hotel Jayapura will increase sales, conversely the lower the quality of services provided to reduce the level of sales in the Swiss-Bel Hotel Jayapura. Customer satisfaction variables also affect the level of sales. It can be seen from the ttabel> thitung (2,038> 1,670) with significantly by 0.012 <0.05. The results of this study showed a significant relationship between customer satisfaction on the level of sales. This means that the higher the level of satisfaction perceived by customers on the Swiss-Bel Hotel Jayapura will increase sales, conversely the lower the satisfaction level of the customers would decrease the level of sales in Swiss-Bel Hotel Jayapura.